An Analysis of the Difficulty of National Examination Test Items - Dea Anisa Yusbet; Rizky Gushendra (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
This study aimed to determine: (1) the items categorized into difficult in English National Examination 2016/2017 (2) learning objectives (indicators) that are categorized into difficult of English National Examination 2016/2017. The subjects of the research is the students of the third grade at State Senior High School 5 Pekanbaru. The samples were randomly selected of 43 students. The data obtained through analyzing the answers of English National Examination 2016/2017. The results showed that (1) the items, categorized into difficult are item 2, item 3, item 5, item 8, item 9, item 11, item 13, item 15, item 20, item 25, item 26, item 31, item 41, item 45, item 46, and item 49. The difficult of learning objective (learning-indicators) were indicator 1, indicator 2, indicator 3, indicator 4, indicator 5, indicator 7, indicator 9, indicator 10, indicator 11, indicator 13, and indicator 14.